HUBUNGAN DUKUNGAN SUAMI DENGAN LAMA PERSALINAN KALA II PADA IBU BERSALIN MULTIPARA - Herny (LPPM STIKes Mitra Adiguna, 2025)
Extended lanour can result in complications such as infection, fatugue, dehydration, and postpartum hemorrhage, which can ultimately lead to the death of the mother. The second stage of labour is a demanding period that necessitates substansial energy expenditure while giving birth. A mother endeavors to give birth to her baby by responding to intense contractions, enabling her to participate in the process actively. The birthing mother’s positive emotions and active engagement contribute to a more tranquil psychological state, facilitating the smooth progression of labour without inducing stress in the baby. It can be achieved by the husband providing assistance and encouragement during the labour process. This study aims to establish the correlation between spousal support and the duration of the second stage of labour in multiparous mothers giving birth at the Pulau Sapi Community Health Centre in 2023. This study employed a correlational analytic strategy utilizing a cross-sectional methodology. The sample size for this study consisted of 26 mothers giving birth at the Pulau Sapi Community Health Centre accompanied by their husbands. Teh sampling process employed a purposive sampling strategy, including 16 respondents. The instrument used for data collection was an observation sheet. The research findings were examined using the Chi-square test, yielding a p-value of 0,001, it indicates that the probability (p) is <0,05, leading to rejecting the null hypothesis (H0). Consiquently, it can be inferred that there is a correlation between the level of support provided by husbands and the duration of the second stage of labour in multiparous birthing women. The research findings indicate that the Husband’s Support significantly impacts the second stage of labour.